2019
DOI: 10.1016/j.celrep.2019.11.093
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of RNA Splicing in Tauopathies

Abstract: SUMMARY Pathological aggregation of RNA binding proteins (RBPs) is associated with dysregulation of RNA splicing in PS19 P301S tau transgenic mice and in Alzheimer’s disease brain tissues. The dysregulated splicing particularly affects genes involved in synaptic transmission. The effects of neuroprotective TIA1 reduction on PS19 mice are also examined. TIA1 reduction reduces disease-linked alternative splicing events for the major synaptic mRNA transcripts examined, suggesting that normalization of RBP functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 71 publications
3
46
0
Order By: Relevance
“…It has also been hypothesized that mutant tau mislocalizes to the somatodendritic compartment, where it alters RBP function (Vanderweyde et al, 2016). In the tau-P301S mouse, aggregation of RBPs with tau, and resulting alterations in splicing, converge on pathways associated with synaptic transmission (Apicco et al, 2019), similar to the effect we observed in tau-V337M organoids. These mice exhibit increased inclusion of exon 14 of the AMPA receptor subunit GRIA2 (Apicco et al, 2019), which we also observed in tau-V337M organoids.…”
Section: Discussionsupporting
confidence: 79%
“…It has also been hypothesized that mutant tau mislocalizes to the somatodendritic compartment, where it alters RBP function (Vanderweyde et al, 2016). In the tau-P301S mouse, aggregation of RBPs with tau, and resulting alterations in splicing, converge on pathways associated with synaptic transmission (Apicco et al, 2019), similar to the effect we observed in tau-V337M organoids. These mice exhibit increased inclusion of exon 14 of the AMPA receptor subunit GRIA2 (Apicco et al, 2019), which we also observed in tau-V337M organoids.…”
Section: Discussionsupporting
confidence: 79%
“…RNA-seq has demonstrated that significant dysfunction on RNA splicing occurs in the PS19 tau mouse model and in AD brain [51]. In addition, reduced expression of an RNA binding protein TIA1 normalized some of the impaired disease-related RNA splicing [51]. Based on the analysis of the…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, loss of dTau, resulted in elevated translation and protein synthesis as reflected by the increased expression of translation machinery components, including initiation factors, proteins which control gene expression or silencing and ribosomal proteins. Spliceosome disruption and altered pre-mRNA processing are also emerging as potential contributors to Tau-mediated neurodegeneration [52] . On the other hand, transgenic Tau elevation by expression of human Tau in the fly CNS, triggered the reduction of multiple spliceosomal proteins [53] .…”
Section: Resultsmentioning
confidence: 99%